Analysis Of Risk Factors For Musculoskeletal Disorders (MSDS) Among Water Depot Workers - Harianja, Linia Oshin Naomi; Pranata, Daffa Wizdan (Open Access Health Scientific Journal, 2025)
Background: Musculoskeletal Disorders (MSDs) are health problems frequently experienced by workers with repetitive and strenuous physical activities, such as manually transporting water gallons at water depots. This study aimed to analyze the relationship between individual factors (age, work duration, and length of service) and ergonomic factors (work posture) with the incidence of MSDs among water depot workers in Indra Kasih Village, Medan City.Methods: This study used quantitative methods with a total sampling of 40 respondents, using questionnaires and direct observation. Data analysis was performed using univariate, bivariate (Chi-Square test), and multivariate methods.Results: The results showed that 25 respondents (62.9%) were diagnosed with MSDs, while 15 respondents (37.5%) were undiagnosed. No significant association was found between age (p=0.622), length of service (p=0.722), or length of service (p=1.000) with the incidence of MSDs. However, there was a significant association between work posture and MSDs (p=0.005, OR=7.071).Conclusion: These findings indicate that unergonomic work postures significantly increase the risk of MSDs. This study recommends ergonomic interventions, the provision of lifting aids, and regular training for workers to minimize the risk of MSDs.